Mathematical literacy levels in a social context: A sociomathematical analysis of eighth-grade middle school students - Nanang Nabhar Fakhri Auliya; Vina Normala; Rizka Kamalia Agustin (Journal Focus Action of Research Mathematic (Factor M), 2026)
Mathematical literacy is recognized as a critical skill in facing the challenges of modern life, and a deep understanding of mathematical literacy at the junior high school level is important to form the basis of mathematical skills that are sustainable and relevant to students' social lives. This research aims to analyze the level of mathematical literacy of class VIII SMP students in a social context using a sociomathematical approach. This research uses descriptive research with a qualitative approach involving interviews, observations, questionnaires, and tests. The sampling technique for this research was purposive sampling with a total of 31 students divided into three main groups (high, medium, and low). Apart from that, the maximum variation sampling technique was also applied to ensure variations in student characteristics, so that the data obtained could describe the phenomenon comprehensively until it reached data saturation. Data analysis in this research uses the Miles and Huberman Model technique. The results of this research reveal that mathematical literacy and socio-mathematical norms support each other in creating meaningful learning. However, the gap between students with high, medium, and low mathematical literacy indicates the need for more inclusive and adaptive learning strategies to ensure that all students can develop optimally.